Mode matters - endurance exercise modes influence changes in EEG resting state brain networks - Büchel, D.; Torvik, P. O.; Lehmann, T.; Sandbakk, Ø.; Baumeister, J. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: Acute bouts of exercise affect the organization of human brain networks transiently and can either improve or deteriorate neural processes underlying sports performance. Exercise intensity is regarded as a key variable in this interaction, since moderate to high intensities facilitate neural processing, while exhaustive exercise seems to impair these processes. Besides intensity, the sensorimotor demands of different exercise modes may further affect modulations of brain networks due to differences in sports-specific techniques or muscles involved. However, exercise mode is barely considered an additional moderator of acute exercise brain interactions. Therefore, this study aimed to explore the effect of exercise mode on transient changes in electroencephalography (EEG) resting state networks (RSNs) comparing running and cross-country (XC) skiing.